Thrips arorai Bhatti (Thysanoptera, Thripidae): first description of the male - Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2015)
Thrips arorai was described from two females collected on fern at Mussoorie, Uttar Pradesh, India (Bhatti 1980). Recently, a series of both sexes of this distinctive brown species with banded fore wings was collected on fern in Himachal Pradesh. Females were identified using published literature (Bhatti 1980, Palmer 1992), and the male is here described for the first time. In the key to males by Palmer, arorai will track to couplet fifty-seven.